Models of Inflammation: Carrageenan‐ or Complete Freund's Adjuvant (CFA)–Induced Edema and Hypersensitivity in the Rat. Issue 1 (1st September 2015) - McCarson, Kenneth E.
Abstract: Animal models of inflammation are used to assess the production of inflammatory mediators at sites of inflammation, the processing of pain sensation at CNS sites, the anti‐inflammatory properties of agents such as nonsteroidal anti‐inflammatory drugs (NSAIDs), and the efficacy of putative analgesic compounds in reversing cutaneous hypersensitivity. Detailed in this unit are methods to elicit and measure carrageenan‐ and complete Freund's adjuvant (CFA)–induced cutaneous inflammation. Due to possible differences between the dorsal root sensory system and the trigeminal sensory system, injections into either the footpad or vibrissal pad are described. In this manner, cutaneous inflammation can be assessed in tissue innervated by the lumbar dorsal root ganglion neurons (footpad) or by the trigeminal ganglion neurons (vibrissal pad). © 2015 by John Wiley & Sons, Inc.